PRAGMATICS IMPOLITENESS STRATEGIES ANALYSIS BASED ON CULPAPER’S THEORY PERSPECTIVE AT TURNING RED MOVIE - Siti Fatimah Nurjanah; Maisa, Haris Budiana (International Journal of Teaching and Learning, 2024)
The pragmatic analysis has become progressively noteworthy in understanding impoliteness strategy in recent years, especially in the movie pragmatics analysis. This study aims to examine the types of impoliteness strategies used in the movie Turning Red. The method of qualitative design is qualified to deal with it. The data was collected by watching the movie repeatedly and taking notes in the conversation. The data were analyzed using impoliteness strategies by the Culpeper framework. The result showed that there are thirteen utterances that consisted of three utterances of bald on record, four utterances of positive impoliteness, five utterances of negative impoliteness, and one utterance identified as sarcasm or mock politeness. However, there is one strategy that is not found in the movie it is withhold politeness.  It means that this movie is intended to show the negative facial desires (turning red) and put the environment in negative situations, interfering with their freedom  of action and humiliation.